Detecting Gravitational-wave Bursts from Black Hole Binaries in the Galactic Center with LISA - Alan M. Knee; Jess McIver; Smadar Naoz; Isobel M. Romero-Shaw; Bao-Minh Hoang; Evgeni Grishin (The Astrophysical Journal Letters, 2024)
Stellar-mass black hole binaries (BHBs) in galactic nuclei are gravitationally perturbed by the central supermassive black hole (SMBH) of the host galaxy, potentially inducing strong eccentricity oscillations through the eccentric Kozai–Lidov mechanism. These highly eccentric binaries emit a train of gravitational-wave (GW) bursts detectable by the Laser Interferometer Space Antenna (LISA)—a planned space-based GW detector—with signal-to-noise ratios up to ∼100 per burst. In this work, we study the GW signature of BHBs orbiting our galaxy’s SMBH, Sgr A ^* , which are consequently driven to very high eccentricities. We demonstrate that an unmodeled approach using a wavelet decomposition of the data effectively yields the time-frequency properties of each burst, provided that the GW frequency peaks between 10 ^−3 and 10 ^−1 Hz. The wavelet parameters may be used to infer the eccentricity of the binary, measuring ${log}_{10}(1-e)$ within an error of 20%. Our proposed search method can thus constrain the parameter space to be sampled by complementary Bayesian inference methods, which use waveform templates or orthogonal wavelets to reconstruct and subtract the signal from LISA data.